The Effectiveness of Tutorial Video-Based Edmodo Learning Media in Hair and Bun Styling Courses - Merita Yanita; Ambiyar Ambiyar; Nurhasan Syah; Syahril Syahril (Jurnal Paedagogy, 2023)
This study analyzes the effectiveness of video tutorial-based Edmodo learning media in Hair and Bun Styling courses. This research method used the Research and Development (R & D) method using the 4D model (Define, Design, Develop, Disseminate). The hypothesis test used in this research was the t-test. The results showed that video tutorial-based learning media was effective, with differences in student learning outcomes between the control and experimental classes. This research has produced an effective tutorial video learning media that can be used to improve students' understanding of the material and practical skills in lectures on learning Hair and Bun Styling. Using video tutorial learning media can increase the effectiveness and efficiency of time use in the learning process to be carried out optimally. Video tutorial-based learning media displayed through the Edmodo application has ease in learning because it can be accessed independently by students and can take advantage of existing technology because it is accessed via students' smartphones and maximizes the use of existing facilities and infrastructure.